Mixed integer programming modeling for the satellite three-dimensional layout optimization problem from two component assignment perspectives - Xia, Yufeng; Chen, Xianqi; Liu, Zhijia; Zhou, Weien; Yao, Wen; Zhang, Zhongneng; Wang, Chenxi (Expert systems with applications, 2025)
•Proposing a novel satellite 3D component assignment and layout optimization problem considering customized distances (cSCALO).•Building MINLP and MILP models for the cSCALO problem, based on cabin module and cabin plate component assignment perspectives.•Proposing a general framework, the virtual component method (VCM), for modeling customized distance constraints.•Verifying the feasibility and effectiveness of the proposed methods by two numerical cases and one engineering case.•Demonstrating the optimal layout results from the engineering case using CAD software. Satellite Component Layout Optimization (SCLO) is crucial for satellite system design. To meet increasingly complex practical requirements, this paper introduces a customized distance-constrained Satellite Component Assignment and Layout Optimization (cSCALO) problem. The objective is to optimize heat dissipation performance while considering constraints on component non-overlap, system static stability, special component position, and the newly proposed customized distance constraint. Compared to previous layout optimization problems, this problem optimizes both continuous position variables and discrete assignment variables, which interact with each other, making it a combinatorial optimization problem with complex multidisciplinary constraints. To address this, two assignment perspectives—cabin module-based and cabin plate-based—are explored, with corresponding Mixed Integer Nonlinear Programming (MINLP) and Mixed Integer Linear Programming (MILP) models developed for each, enabling a comparison of different constraint modeling approaches. For the customized distance constraints in models, this paper proposes the Virtual Component Method (VCM), which explicitly transforms these constraints into non-overlapping constraints between virtual and actual components, providing a generalized framework. Finally, the feasibility and effectiveness of the proposed methods are verified by comparing i) different modeling approaches for customized distance constraints, ii) nonlinear and linear models, and iii) different component assignment perspectives, using two numerical cases and one engineering case.